2015
DOI: 10.1038/npp.2015.103
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the Role of Infralimbic Cortex in Learning and Consolidation of Extinction of Recent and Remote Aversion Memory

Abstract: Medial prefrontal circuits have been reported to undergo a major reorganization over time and gradually take a more important role for remote emotional memories such as contextual fear memory or food aversion memory. The medial prefrontal cortex, and specifically its ventral subregion, the infralimbic cortex (IL), was also reported to be critical for recent memory extinction of contextual fear conditioning and conditioned odor aversion. However, its exact role in the extinction of remotely acquired information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 67 publications
6
32
2
Order By: Relevance
“…However, the involvement of its subregions in remote fear memory extinction remains elusive. While the roles of the infralimbic cortex (IL) and anterior cingulate cortex (ACC) were directly tested and showed controversial results (Vetere et al 2012 ; Rosas-Vidal et al 2014 ; Awad et al 2015 ), activity in the prelimbic cortex (PL) was never directly assessed during remote fear memory extinction despite its well-established role in the fear memory circuit (Frankland and Bontempi 2005 ). Moreover, specific molecular changes within the retrosplenial cortex (RSP) have been linked to remote fear memory extinction (Corcoran et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of its subregions in remote fear memory extinction remains elusive. While the roles of the infralimbic cortex (IL) and anterior cingulate cortex (ACC) were directly tested and showed controversial results (Vetere et al 2012 ; Rosas-Vidal et al 2014 ; Awad et al 2015 ), activity in the prelimbic cortex (PL) was never directly assessed during remote fear memory extinction despite its well-established role in the fear memory circuit (Frankland and Bontempi 2005 ). Moreover, specific molecular changes within the retrosplenial cortex (RSP) have been linked to remote fear memory extinction (Corcoran et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that the temporal shift in the circuits mediating memory retrieval is mirrored by an analogous shift in extinction circuits. For example, unlike the infralimbic cortex (IL), which is involved during both recent and remote extinction (Vetere et al 2012 ; Rosas-Vidal et al 2014 ; Awad et al 2015 ) molecular adaptations in the retrosplenial cortex are only necessary for remote extinction (Corcoran et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This point was emphasized in a recent study comparing the role of the IL cortex in the extinction of two different aversive learning paradigms; contextual fear conditioning and conditioned odor aversion. The study found that while the IL cortex is necessary for the consolidation of extinction training of recent and remote contextual fear memories, it is only involved in the consolidation of extinction training for recent conditioned odor aversion (Awad et al, 2015). Thus, this study provides an example of how the same brain region could uniquely contribute to the extinction in two different aversive learning paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments it is noteworthy that theta power in the vmPFC specifically increases when the animal reaches the “safe” areas of anxiogenic environments, which has been interpreted as a mechanism for behavioural inhibition. In this context, IL theta rhythm seems to play a crucial role in fear extinction and stress control (Thompson et al, ; Awad, Ferreira, & Maroun, ; Ronzoni, Antón, Mora, Segovia, & Del Arco, ). Indeed corticolimbic theta coupling between the IL and the lateral amygdala has been described for fear extinction conditions, and is considered an example of adaptive inhibitory learning (Lesting et al, ).…”
Section: Discussionmentioning
confidence: 99%